Is there an associational resistance of winter pea–durum wheat intercrops towards Acyrthosiphon pisum Harris?. (10th February 2014) - Ndzana, R. A.; Magro, A.; Bedoussac, L.; Justes, E.; Journet, E.‐P.; Hemptinne, J.‐L.
Abstract Acyrthosiphon pisum Harris (Aphididae: Hemiptera), the pea aphid, is an important pest in organic farming systems. In this work, the objective was to gather empirical field data on the associational resistance of durum wheat–winter pea intercrops towards the pea aphid, compared with pure stands of winter pea. Our results showed that intercropping winter pea with durum wheat significantly decreased A. pisum abundance in all the situations. Moreover, it was systematically observed that pea grew bigger in pure than in intercropped stands but after considering pea dry mass as a covariate, it appeared that the durum wheat–winter pea intercrop was still significantly less attacked by pea aphids than the sole crop. Intercrop sowing designs had an incidence on infestation levels: substitutive diversification systems of different types are more effective in decreasing the level of aphid infestation than does the additive system. In addition, substitutive row intercrop is significantly less infested than substitutive mixture. These results suggest that a mechanism related to the resource concentration hypothesis may explain the associational resistance of the IC of durum wheat–winter pea towards A. pisum.